Formulation and Application of Molasses-Based Bacterial Consortium to Degrade Waste Oil and Fat in the Environment - Kawuri, Retno; Darmayasa, Ida Bagus Gede; Widyastama, I Komang Adi; Putri, Rochmalia Juniarti (Metamorfosa: Journal of Biological Sciences; Vol 10 No 2 (2023)DO - 10.24843/metamorfosa.2023.v10.i02.p12, 2023)
Pollution of fat waste into the aquatic environment originating from industrial food processing, restaurants and kitchens or by accidental oil spills is currently being found more and more. PUPS results for 2020 found 3 bacterial strains, namely Bacillus licheneformis, Bacillus coagulan and Pseudomonas diminuta . The microbial consortium is a mixture of microbial populations in the form of communities that have cooperative, commensal, and mutualistic relationships. Field tests need to be carried out to test whether the results of the degradation of fats and oils from the three bacteria above can be applied to waste fats and oils in the environment. The purpose of this study was to find media formulations and proper applications from molasses-based bacterial consortia and to determine the effectiveness of molasses-based media formulations. This study used the Sequence Batch Reactor (SBR) method, physical, chemical and biological parameters including measurement of total fat, Dissolve Oxygen/DO Test, BOD 5 Test (Biological Oxygent Demant), Nitrate Test, Nitrite Test Total dissolved solids (Total dissolve solid/TDS), and TPC Microbial Count, (Total Plate Count). The results showed a decrease in the treatment of bacterial consortium of 80 ml/2lt (40 ml/lt) of waste fats and oils on measurements of BOD5, TDS, total fat, nitrite and nitrate and the bacterial population remained high on the 5th day after treatment. This study demonstrated the ability of a molasses-based bacterial consortium to be used as a starter agent for processing fat waste in an environment polluted by fat and oil waste.